Ethanol Extract Antioxidant Activity Test of Tembelekan (Lantana camara L.) using 1,1-diphenyl-2-picrylhydrazyl (DPPH) Reagent - Sitti Aminah; Evi R. Amelia (Universitas Tadulako, 2022)
The plant prickly lantana (Lantana Camara L.) contains alkaloids, flavonoids, saponins, tannins, and triterpenoids and has the potential to be used as a natural antioxidant source. The research objective is to determine the IC50 value for the antioxidant activity of prickly lantana leaf extract. Prickly lantana leaves were macerated in a 96% ethanol solvent for 3x24 hours. Phytochemical analysis of prickly lantana leaves revealed that the leaves contained alkaloids, flavonoids, saponins, and tannins. This antioxidant activity test was performed using the reagent 1,1-diphenyl-2-picrylhydrazyl (DPPH), whose absorption at 517 nm was measured using a UV-Vis spectrophotometer, and by varying the sample concentration after the addition of prickly lantana leaf extract. The concentrations of prickly lantana leaf extract used varied from 20 ppm to 40 ppm, 60 ppm, and 80 ppm. The positive control was vitamin C at the same concentration variation, and the negative control was DPPH solution dissolved in 96% ethanol. The results showed that the IC50 of prickly lantana leaf extract was 164.639 ppm, while vitamin C had an IC50 of 18.754 ppm.